"We are an active family": a randomized trial protocol to evaluate a family-system social identity intervention to promote child physical activity - Evangeline Streight; Mark R. Beauchamp; Kurt J. Smith; Chris M. Blanchard; Valerie Carson; Shaelyn M. Strachan; Leigh M. Vanderloo; Sandy Courtnall; Ryan E. Rhodes (BMC, 2024)
Abstract Background Regular engagement in moderate-to-vigorous physical activity (MVPA) during childhood yields a myriad of health benefits, and contributes to sustained MVPA behaviors into adulthood. Given the influence of parents on shaping their child's MVPA behaviour, the family system represents a viable target for intervention. The purpose of this study is to compare the effects of two intervention conditions designed to increase child MVPA: (1) A standard education + planning intervention providing information about benefits, action planning, and coping planning; and (2) An augmented physical activity education + planning intervention that includes the components of the standard intervention, as well as a focus on family identity promotion and developing as an active member of the family. Methods A two-arm parallel single-blinded randomized trial will compare the two conditions over 6 months. Eligible families have at least one child aged 6-12 years who is not meeting the physical activity recommendations within the Canadian 24-Hour Movement Guidelines (i.e.,<60 min/day of MVPA). Intervention materials targeting family identity promotion will be delivered online via zoom following baseline assessment, with booster sessions at 6-weeks and 3-months. Child MVPA will be measured by wGT3X-BT Actigraph accelerometry at baseline, 6-weeks, 3-months, and 6-months as the primary outcome. At these same time points, parent cognition (e.g., attitudes, perceived control, behavioral regulation, habit, identity) and support behaviours, and parent-child co-activity will be assessed via questionnaire as secondary outcomes. Child-health fitness measures will be also administered through fitness testing at baseline and 6-months as secondary outcomes. Finally, upon completion of the trial's 6-month measures, a follow-up end-of-trial interview will be conducted with parents to examine parents' experiences with the intervention. Results So far, 30 families have been enrolled from the Southern Vancouver Island and Vancouver Lower Mainland area. Recruitment will be continuing through 2026 with a target of 148 families. Discussion This study will contribute to the understanding of effective strategies to increase child physical activity by comparing two intervention approaches. Both provide parents with education on physical activity benefits, action planning, and coping planning supports. However, one intervention also incorporates components focused on promoting an active family identity and involving all family members in physical activity together. The findings from this study have the potential to inform the design and implementation of public health initiatives aimed at improving physical activity participation in children and guide the development of more effective interventions that leverage the crucial role of parents and the family system in shaping children's physical activity behaviors. Trial Registration The clinical trial registration ID is NCT05794789. This trial was registered with clinicaltrials.gov on March 2nd, 2023, with the last updated release on September 28th, 2023.